Adaptive Survival Strategies Amid Energy Transition and Price Volatility: Case Study of PESTEL Integration - SWOT and Dynamic Capability in PT ABC Coal Traders - Yudhi Putro (Publikasi Indonesia, 2025)
This study aims to test and formulate adaptive survival strategies for medium-scale coal trading companies in Indonesia that face price volatility, energy regulation, and global market uncertainty. Using the case study of PT ABC (an independent trader without mining assets), a qualitative approach was applied through a semi-structured FGD of two 120-minute sessions with six internal informants (four core management, one administrative staff, and one field staff). The analysis was carried out sequentially: PESTEL assessed external pressures, SWOT mapped strengths and weaknesses, and then Dynamic Capabilities and McKinsey 7S evaluated the organization's adaptation readiness. The results show that PT ABC excels in supply network and operational flexibility but is weak in internal governance and HR structure. A defensive strategy is recommended: operational efficiency, strengthening of organizational functions, and asset-light limited export expansion. This study enriches the literature by integrating an external-internal framework for independent commodity traders and opens up research space on the relationship between adaptive organizational structure and the success of survival strategies in the transitional fossil energy sector.